Green innovations and their town applications - Janiszek, Monika (Research Papers of Wrocław University of Economics, 2018)
Actions that are environmentally friendly are increasingly being undertaken by private organizations, the public entities and the community. This process strives to meet the needs of society and to maintain balance between the natural environment and the economic activity. One of the solutions is sustainable building for energy efficient buildings, waste recycling and water saving and in addition, the use of renewable energy, regional materials and raw materials, recycled and environmentally friendly, as well as the promotion of bicycles and public transport. The process of making a dialogue between the local authority and residents is supported by spatial information acquisition and processing technologies and Internet communication tools The aim of the article is to analyze the resource-efficient and effective projects implemented in the city and to indicate the benefits for the economy. These benefits are to be achieved through green innovations that combine innovation with environmental sensitivity and ecological awareness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 502, s. 85-94
Keywords: sustainable business; green innovations; sustainable development; urban applications; geographical information systems; zrównoważony biznes; innowacje ekologiczne; zrównoważony rozwój; aplikacje miejskie; systemy informacji geograficznej